Autoregulation of cardiac output is overcome by adrenergic stimulation in the anaconda heart - Joyce, William; Axelsson, Michael; Wang, Tobias (Journal of experimental biology, 2017)
Most vertebrates increase cardiac output during activity by elevating heart rate with relatively stable stroke volume. However, several studies have demonstrated 'intrinsic autoregulation' of cardiac output where artificially increased heart rate is associated with decreased stroke volume, leaving cardiac output unchanged. We explored the capacity of noradrenaline to overcome autoregulation in the anaconda heart. Electrically pacing in situ perfused hearts from the intrinsic heart rate to the maximum attainable resulted in a proportional decrease in stroke volume. However, noradrenaline, which increased heart rate to the same frequency as pacing, maintained stroke volume and thus increased cardiac output. In atrial and ventricular preparations, noradrenaline significantly increased the force of contraction and contraction kinetics. Thus, the increased contractility associated with adrenergic stimulation ameliorates filling limitations at high heart rates. Although heart rate appears the primary regulated variable during activity, this may only be achieved with compensatory amendments in myocardial contractility provided by adrenergic stimulation.